1998
DOI: 10.1038/2464
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal maternal behaviour and growth retardation associated with loss of the imprinted gene Mest

Abstract: Mest (also known as Peg1), an imprinted gene expressed only from the paternal allele during development, was disrupted by gene targeting in embryonic stem (ES) cells. The targeted mutation is imprinted and reversibly silenced by passage through the female germ line. Paternal transmission activates the targeted allele and causes embryonic growth retardation associated with reduced postnatal survival rates in mutant progeny. More significantly, Mest-deficient females show abnormal maternal behaviour and impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
441
3
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 531 publications
(470 citation statements)
references
References 38 publications
20
441
3
6
Order By: Relevance
“…The maternally expressed Phlda2/Ipl acts to restrain placental growth while the paternally expressed Mest promotes it [51,52]. Apostolidou et al [53] screened 200 human placentas by qPCR for PHLDA2, IGF2, IGF2R and MEST.…”
Section: The Role Of Placental Imprinted Gene Expression In Developmementioning
confidence: 99%
“…The maternally expressed Phlda2/Ipl acts to restrain placental growth while the paternally expressed Mest promotes it [51,52]. Apostolidou et al [53] screened 200 human placentas by qPCR for PHLDA2, IGF2, IGF2R and MEST.…”
Section: The Role Of Placental Imprinted Gene Expression In Developmementioning
confidence: 99%
“…Imprinted genes may regulate some of the crucial aspects of mammalian physiology associated with reproduction, placentation, energy homeostasis, lactation and behaviour [16][17][18] . For example, Igf2, which encodes a fetal insulin-like growth factor 2, is repressed in the maternal genome and active only in the paternal genome 19 .…”
Section: Epigenetic Asymmetry Between Parental Genomesmentioning
confidence: 99%
“…One of the first such studies 155" involved the paternally expressed gene Peg1/Mest on mouse chromosome 6. Although a 156" paternally inherited mutation in this gene results in reduced weight at birth, this deficit is 157" subsequently exacerbated by reduced post-natal growth rate relative to wild-type littermates 158" (Lefebvre et al, 1998). This suggested that imprinted genes not only regulate resource 159" extraction during gestation, but could also influence offspring physiology or behavior post-160" natally.…”
Section: Imprinted Gene Effects In Offspring 151"mentioning
confidence: 99%
“…As well as affecting offspring, deletion of paternally expressed Peg1/Mest also affects 194" female maternal care (Lefebvre et al, 1998). Pups born to mutant mothers suffer elevated 195" post-natal mortality, even if they are wild-type offspring with a normal paternal Peg1/Mest 196" allele.…”
Section: "mentioning
confidence: 99%
See 1 more Smart Citation